Drug Discovery Testing Compounds in Patient Samples by Automated Flow Cytometry. (June 2017) - Hernández, Pilar; Gorrochategui, Julián; Primo, Daniel; Robles, Alicia; Rojas, José Luis; Espinosa, Ana Belén; Gómez, Cristina; Martínez-López, Joaquín; Bennett, Teresa A.; Ballesteros, Joan
Functional ex vivo assays that predict a patient's clinical response to anticancer drugs for guiding cancer treatment have long been a goal, but few have yet proved to be reliable. To address this, we have developed an automated flow cytometry platform for drug screening that evaluates multiple endpoints with a robust data analysis system that can capture the complex mechanisms of action across different compounds. This system, called PharmaFlow, is used to test peripheral blood or bone marrow samples from patients diagnosed with hematological malignancies. Functional assays that use the whole sample, retaining all the microenvironmental components contained in the sample, offer an approach to ex vivo testing that may give results that are clinically relevant. This new approach can help to predict the patients' response to existing treatments or to drugs under development, for hematological malignancies or other tumors. In addition, relevant biomarkers can be identified that determine the patient's sensitivity, resistance, or toxicity to a given treatment. We propose that this approach, which better recapitulates the human microenvironment, constitutes a more predictive assay for personalized medicine and preclinical drug discovery.